Groundwater nitrate response to hydrogeological conditions and socioeconomic load in an agriculture dominated area - Hui Jia; Hui Qian (Scientific Reports)
Abstract Nitrate pollution is widespread environmental concern in most shallow groundwater systems. This study conducts a comprehensive investigation of shallow groundwater, deep groundwater, and surface water in a region of the Chinese Loess Plateau. Nitrate pollution in this area is severe with more than half of the shallow groundwater samples exceeding the limit of nitrate for drinking water (50 mg/L). Temporal variation of nitrate reveals a continued increase of nitrate in shallow groundwater, although the fertilizer use has been reduced, recently. Spatially, deep groundwater nitrate is much lower than that in shallow groundwater, supporting the anthropogenic origin of nitrate from surface. The intrinsic vulnerability index indicates less susceptibility of loess aquifer to pollution in comparison to alluvial aquifer. However, high levels of nitrate are observed in both alluvial and loess aquifers. The pollution risk assessment combined with anthropogenic loads explains the occurrence of nitrate more precisely. Agricultural inputs and release of sewage-effluents are the major contributions of nitrate from hydrogeochemical evidence. The high nitrate in loess aquifer, which is supposed to be less susceptible to contamination, indicates anthropogenic loads to be a non-negligible factor. Control of nitrate pollution in loess area is long-standing issue and will require sustained monitoring.